2015
DOI: 10.1614/ws-d-14-00150.1
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing Potential between U.S. Blackhull Red Rice and Indica Rice Cultivars

Abstract: Weedy red rice is a major weed pest of rice in the southern United States. Outcrossing between red rice and commercial tropical japonica rice cultivars has resulted in new weed biotypes that further hinder the effectiveness of weed management. In recent years, indica rice has been used increasingly as a germplasm source for breeding and for reduced-input systems in the United States, but little is known about its outcrossing potential with U.S. weedy red rice biotypes. In a 2-yr study, simple sequence repeat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Conversely, 96% of the black hull accessions had an awn. These findings are similar to those found by Burgos et al (2014) and Gealy et al (2015) when assessing the phenotypic characteristics of weedy rice accessions across the mid-South. The majority of weedy rice in the midsouthern United States is straw hull in color and does not bear awns, whereas those that are black hull in color will most likely have an awn.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, 96% of the black hull accessions had an awn. These findings are similar to those found by Burgos et al (2014) and Gealy et al (2015) when assessing the phenotypic characteristics of weedy rice accessions across the mid-South. The majority of weedy rice in the midsouthern United States is straw hull in color and does not bear awns, whereas those that are black hull in color will most likely have an awn.…”
Section: Resultssupporting
confidence: 91%
“…Highly competitive and difficult to control in a cultivated rice system, weedy rice can in some cases lead to total crop failure and reduced milling quality (Burgos et al 2006). Gealy et al (2015) reported that US weedy rice populations can be divided phenotypically and evolutionarily into two distinct groups: straw hull (awnless) and black hull (awned).…”
Section: Introductionmentioning
confidence: 99%
“…Outcrossing rates in cultivated rice are estimated to be less than one per cent (Messeguer et al ., ); however, figures well above twenty per cent have been reported for crosses between cultivated and wild rice species when grown in specific conditions (Marathi and Jena, ; Phan et al ., ). Cross‐pollination between cultivated species and weedy wild relatives is problematic to rice producers as it may hinder the effectiveness of weed management and/or lead to the loss of favourable traits in a given line (Gealy et al ., ). For example, Clearfield ® rice is a commercial, nontransgenic variety of rice which is resistant to a herbicide called imazethapyr.…”
Section: Introductionmentioning
confidence: 97%
“…However, introgression from cultivated rice into weedy rice has been detected in both SH and BHA ecotype backgrounds (see InStruct mix group from Reagon et al ., ). There is also evidence of hybridisation between BHA rice and some late flowering indica cultivars based on field trials (Gealy et al ., ), indicating that crop–weed introgression is possible. Outcrossing rates between transgenic lines of cultivated rice and weedy rice in field trials have been measured between 0 and 6.66% (Zuo et al ., ).…”
Section: Introductionmentioning
confidence: 99%